PANDEMIC COVID-19, BODY IMMUNITY RESPONSE, AND HERD IMMUNITY - Handayani, Rina Tri; Arradini, Dewi; Darmayanti, Aquartuti Tri; Widiyanto, Aris; Atmojo, Joko Tri (LPPM STIKES KENDAL, 2020)
The World Health Organization has stated that COVID-19 is a